Cardiology Rx for Change: Improving Clinical Attention to Tobacco Use and Secondhand Smoke Exposure in Cardiology - Prochaska, Judith J. (Clin Cardiol, 2011)
BACKGROUND: Heart disease is the leading cause of tobacco‐related death in smokers and of deaths due to secondhand smoke (SHS) exposure in nonsmokers. This study centers on the development and evaluation of an evidence‐based model curriculum for improving clinical attention to tobacco use and SHS exposure in cardiology. HYPOTHESIS: We hypothesized that the curriculum would be associated with improvements in clinician tobacco‐related knowledge, attitudes, confidence, and counseling behaviors from pre‐to post‐training and at the 3‐month follow‐up. METHODS: The 1‐hour Cardiology Rx for Change curriculum was evaluated with 22 cardiology fellows and 77 medical residents with consistent training effects observed between the 2 groups. RESULTS: Trainees' tobacco treatment knowledge increased significantly from pre‐ to post‐training (t[81] = 6.51, P<0.001), and perceived barriers to providing cessation treatment decreased significantly (t[81] = −3.97, P<0.001). The changes, however, were not sustained at the 3‐month follow‐up, suggesting the need for booster training efforts. From pretraining to 3‐month follow‐up, the training was associated with significant sustained gains in clinician confidence for treating tobacco dependence (t[61] = 3.69, P = 0.001) and with improvements in clinicians assessing patients' readiness to quit smoking (from 61% to 79%, t[59] = 3.69,P<0.001) and providing assistance with quitting (from 47% to 59%, t[59] = 2.12, P = 0.038). Asking patients about tobacco use, advising cessation, and arranging follow‐up also increased over time, but not significantly. All participants (100%) recommended the curriculum for dissemination to other training programs. CONCLUSIONS: Available online via http://rxforchange.ucsf.edu, Cardiology Rx for Change offers a packaged training tool for improving treatment of tobacco use and SHS exposure in cardiology care. © 2011 Wiley Periodicals, Inc. This work was supported by the Flight Attendant Medical Research Institute (FAMRI) William Cahan Distinguished Professor Award (PI: W. Grossman), and the State of California Tobacco‐Related Disease Research Program (# 17RT‐0077, PI: J.J. Prochaska). The authors have no other funding, financial relationships, or conflicts of interest to disclose.